Miguel Antonio Caro y el pensamiento conservador ante las independencias hispanoamericanas (2010)
ABSTRACT: During XIX century, the pelomical ideologies about conquer and colonization of America were intensified among the Latin American elites. A clear example was that of the orthodox conservative man called Miguel Antonio Caro (1843-1909), an active member of the Nationalist “Regeneration” Party executor and main promoter of the “1886 Constitution”. His political project conceived as missionary and patriotic was controversial. His political project intended to keep Spanish heritage and reject independence demanded by many radical liberals of the continent for reaching development and civilization of our peoples. This articles evaluates the main ideas Caro had before the socialpolitical problem of Latin American independences, his passionate controversy while defending Spain as a means for recovering Hispanic civilization in our territories. After over 200 years of our identity and nationality, based on one of the distinguished leaders and defenders of our Latin American thinking.